Perspectives of healthcare providers in family planning centers on increasing pre-exposure prophylaxis uptake among women who have migrated from sub-Saharan Africa to France - Geoffroy Liegeon; Samantha A. Devlin; Victoria Manda; Julie Castaneda; Myriam Toribio; Sophie Florence; Jessica P. Ridgway; Amy K. Johnson (PLoS ONE, 2025)
Pre-exposure prophylaxis (PrEP) for HIV remains largely underused among women who have migrated from sub-Saharan Africa (WMSSA), despite their accounting for a significant proportion of new HIV diagnoses in France and Western European countries. To expand PrEP reach, we explored healthcare providers’ perspectives on PrEP implementation within family planning centers (FPCs) in the Paris region through focus groups. The focus group discussion guide and rapid content analysis were informed by the Consolidated Framework for Implementation Research (CFIR) 2.0, which uses five domains to capture implementation determinants (Innovation, Outer Setting, Inner Setting, Individuals, and Implementation Process). Twenty providers participated across five focus groups and one key informant interview (median age 45; 80% women, 70% physicians). Oral PrEP was seen as easy to prescribe, but providers advocated for choices beyond the daily pill for better acceptability. While providers recognized increased HIV prevention needs among WMSSA, they found low PrEP demand among women stemming from a lack of knowledge. Although providers acknowledged that PrEP aligned with FPC missions, they cited significant implementation barriers, including limited resources, staff shortages, insufficient on-site capacity, competing priorities, and physicians being the sole prescribers. Provider-level implementation challenges included insufficient training and discomfort in discussing HIV risk and PrEP with WMSSA. Recommendations for implementing PrEP within FPCs included provider training and mentorship, tailored information campaigns for WMSSA, flexible delivery processes, support groups for women, and authorizing midwives and nurses to prescribe PrEP. These results support the need for tailored and multi-level implementation strategies to increase PrEP uptake among WMSSA attending FPCs in France.